Interior view of the Burgtheater in Vienna - Unknown:::Creator::::::::::::; Geissler, Maria (publisher)::::::::::::::: (Austria; Vienna; Maria Geissler)
Color engraving of the interior of the Burgtheater in Vienna, showing the bench seats, balcony seats and boxes, and part of the orchestra pit and the stage.